Investigating spatial distribution of kindergartens in Chinese cities: A spatial stratified heterogeneity approach - Bo Zhang; Shixiong He; Lei Jiang (PLoS ONE, 2026)
The spatial equity of kindergarten distribution is a critical concern for China’s educational policy. This study investigates the socioeconomic determinants underlying the spatial stratification of kindergartens across 323 Chinese cities. Utilizing a spatial stratified heterogeneity framework, we employed web-crawling techniques to gather kindergarten location data and applied Geographical Detector (GD) analysis complemented by Pearson correlation and Grey relational degree methods to quantify the influence and interactions of key factors. Our principal results indicate that: (1) The distribution of kindergartens is highly aggregated in affluent eastern coastal regions, but this pattern becomes more scattered when normalized per capita, revealing disparities in access. (2) Economic capacity (per capita income) and educational attainment (average years of education) are the two most powerful single factors (q-statistics of 0.351 and 0.343, respectively) explaining the spatial distribution. (3) Critically, interaction effects between factors—particularly between income and marriageable population or education levels—are shown to be non-linearly enhanced, meaning their combined effect is stronger than the sum of their individual parts. This study’s main contribution is a robust, methodologically novel empirical analysis that moves beyond linear assumptions to identify the synergistic drivers of kindergarten distribution. We conclude that policy makers must prioritize interventional strategies that simultaneously address economic and educational development to effectively reduce spatial inequities in preschool education access. Moreover, regional economic support policies or targeted public investment in kindergartens could bridge the gaps between urban and rural areas and promote more equitable access to preschool education.